Preparation method and application of Pd-RuCoOx nanoparticles

By using Co elements and a small amount of Ru and Pd, the Pd-RuCoOx nanoparticles were designed and prepared, and the problems of high cost and poor stability of precious metal catalysts were solved, and efficient catalytic activity and stability under acidic conditions were achieved, reducing the amount of precious metals used. Suitable for the acidic decomposition of water-induced oxygen semi-reaction in hydrogen production by water electrolysis.

CN119221025APending Publication Date: 2024-12-31BONAI (SUZHOU) HYDROGEN ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411307315.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Precious metal-based catalysts are expensive and are facing serious dissolution and degradation problems in highly corrosive and oxidative acidic environments, which limits their application in water electrolysis to produce hydrogen.

Method used

The cheap and easy-to-get Co elements are used as the main material, and a small amount of precious metals Ru and Pd are added to design and prepare high-dispersible and uniform size Pd-RuCoOx nanoparticles through an interface induction strategy to serve as a high-efficiency catalyst with low precious metal loading.

Benefits of technology

An OER catalyst with high catalytic activity and stability under acidic conditions is achieved, reducing the amount of precious metals used, reducing costs, and showing excellent performance in the acidic decomposition water oxygen analysis semi-reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119221025A_ABST
    Figure CN119221025A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of Pd-RuCoOx nano-particles, the main components of the Pd-RuCoOx nano-particles are RuO2, Pd and Co3O4, the method uses a simple interface induction strategy, the Pd-RuCoOx nano-particles with high dispersibility and uniform size are designed and synthesized, the preparation process is simple, large-scale preparation is easy, and the Pd-RuCoOx nano-particles are suitable for industrial production. The obtained nanoparticles are uniform in size, good in crystallinity, good in catalytic performance and stability and suitable for an acidic oxygen evolution system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrocatalytic oxygen evolution, and specifically relates to a preparation method and application of Pd-RuCoOx nanoparticles. Background Art

[0002] With the development of society, the consumption of earth's energy is accelerating, so it is of great significance to seek sustainable energy to replace fossil fuel supply. Hydrogen energy has attracted much attention as a sustainable energy with high mass ratio, high energy density and clean and pollution-free. The combination of water electrolysis and renewable energy (solar energy, wind energy, etc.) is considered to be one of the most promising solutions to solve the imminent energy crisis and environmental problems. Traditional alkaline water electrolyzers (AWE) have attracted attention, but a series of problems such as high cost of membranes in alkaline electrolyzers and low overall power density have stagnated their development. Recently, proton exchange membrane water electrolyzers (PEMWEs) that are easy to assemble with renewable energy have become a new generation of candidates due to their high power density, high efficiency at low temperatures and low gas permeability. At present, precious metal-based materials (Pt and Ir, Ru oxides) are the benchmark catalysts for oxygen evolution reaction (OER). However, their scarcity and high cost limit their practical applications. Therefore, it is urgent to develop OER catalysts with low precious metal loading, simple preparation methods, high catalytic activity and stability under acidic conditions. Summary of the invention

[0003] Technical problems to be solved: The purpose of the present invention is to solve the problem that precious metal-based catalysts are expensive and that they face serious dissolution and degradation problems in highly corrosive and oxidative acidic environments. Therefore, the cheap and readily available Co element is selected as the main material, a small amount of precious metals Ru and Pd are added to improve the catalytic activity, and a simple interface induction strategy is used to design and synthesize Pd-RuCoOx nanoparticles with high dispersibility and uniform size, and the main components are RuO2, Pd and Co3O4, providing a preparation method for Pd-RuCoOx nanoparticles with high catalytic activity and stable performance.

[0004] Technical solution: A method for preparing Pd-RuCoOx nanoparticles, comprising the following steps: S1. Weigh sodium tetrachloropalladate and dissolve it in concentrated hydrochloric acid, dilute it with deionized water, and then add cobalt chloride and ruthenium chloride to form a uniform solution A; S2. Prepare an ethanol solution containing oleylamine and mix it evenly with the solution obtained in step S1 to obtain a solution B; S3. Add toluene to solution B, stir thoroughly, transfer to a separatory funnel and take the organic solvent layer; S4. The organic solvent layer obtained in step S3 is placed in an autoclave for a solvothermal reaction to obtain a solid component; S5. Collect the solid components in step S4, clean them, and dry them to obtain a powder material for later use; S6. The powder material obtained in step S5 is placed in a muffle furnace and calcined to obtain Pd-RuCoOx nanoparticles. Furthermore, in step S1, the molar ratio of sodium tetrachloropalladate to ruthenium chloride is 1:1-1:3, the feeding concentration of sodium tetrachloropalladate is 0.001-0.01M, the feeding concentration of ruthenium chloride is 0.001-0.03M; and the concentration of cobalt chloride is 0.01-0.05M. Furthermore, the content of oleylamine in the ethanol solution in step S2 is 5-20%; the ratio of the ethanol solution containing oleylamine to the solution A obtained in step S1 is 1:1. Furthermore, in step S3, the volume ratio of toluene to solution B is 1:1. Furthermore, the temperature of the solvent thermal reaction in step S4 is 180-220° C., and the reaction time is 24-30 hours. Furthermore, in step S5, the drying temperature is 60-80° C., and the drying time is 6-12 hours. Furthermore, in step S6, the calcination temperature is 300-500° C., the calcination time is 2-4 hours, and the heating rate is 2-5° C. / min. Furthermore, the diameter of the Pd-RuCoOx nanoparticles is ≤500nm. Furthermore, the Pd-RuCoOx nanoparticles are used in oxygen evolution reaction in an acidic environment. Beneficial effects: 1. The Pd-RuCoOx nanoparticles prepared by the present invention mainly contain RuO2, Pd and Co3O4, and have the advantages of low precious metal content, regular morphology, uniform size, good controllability, mild reaction conditions, and environmental friendliness; 2. The Pd-RuCoOx nanoparticles prepared in the present invention have high acidic OER catalytic activity at a current density of 10 mA / cm 2 The best potential can reach 1.502V; 3. The present invention can obtain a method for preparing Pd-RuCoOx nanoparticles for acidic water decomposition oxygen evolution half reaction, which reduces the cost by reducing the usage of precious metals Pd and Ru. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 Schematic diagram of the synthesis of Pd-RuCoOx nanoparticles; Figure 2 The X-ray diffraction (XRD) pattern of Pd-RuCoOx-1 prepared in Example 1; Figure 3The scanning electron microscope (SEM) spectrum of Pd-RuCoOx-1 prepared in Example 1; Figure 4 The linear voltammetry (LSV) diagram of Pd-RuCoOx-1 prepared in Example 1; Figure 5 The Tafel diagram of Pd-RuCoOx-1 prepared in Example 1; Figure 6 It curve of Pd-RuCoOx-1 prepared in Example 1; Figure 7 The XRD pattern of Pd-RuCoOx-2 prepared in Example 2; Figure 8 This is the SEM image of Pd-RuCoOx-2 prepared in Example 2; Fig. 9 LSV diagram of Pd-RuCoOx-2 prepared in Example 2; Fig.10 The Tafel diagram of Pd-RuCoOx-2 prepared in Example 2; Fig.11 It curve of Pd-RuCoOx-2 prepared in Example 2; Fig.12 XRD pattern of Pd-RuCoOx-3 prepared in Example 3; Fig.13 This is the SEM image of Pd-RuCoOx-3 prepared in Example 3; Fig.14 LSV diagram of Pd-RuCoOx-3 prepared in Example 3; Fig.15 The Tafel diagram of Pd-RuCoOx-3 prepared in Example 3; Fig.16 It curve of Pd-RuCoOx-3 prepared in Example 3; Fig.17 XRD pattern of Pd-CoOx prepared in Comparative Example 1; Fig.18 This is the SEM image of Pd-CoOx prepared in Comparative Example 1; Fig.19 LSV diagram of Pd-CoOx prepared in Comparative Example 1; Fig. 20 The Tafel diagram of Pd-CoOx prepared in Comparative Example 1; Fig.21 It curve of Pd-CoOx prepared in Comparative Example 1 Fig. 22 XRD pattern of RuCoOx prepared in Comparative Example 2; Fig.23 This is the SEM image of RuCoOx prepared in Comparative Example 2; Fig.24 LSV diagram of RuCoOx prepared in Comparative Example 2; Fig.25 Tafel diagram of RuCoOx prepared in Comparative Example 2; Fig.26 It curve of RuCoOx prepared in Comparative Example 2; Fig. 27 XRD pattern of CoOx prepared in Comparative Example 3; Fig.28 This is the SEM image of CoOx prepared in Comparative Example 3; Fig.29 LSV diagram of CoOx prepared in Comparative Example 3; Fig.30 The Tafel diagram of CoOx prepared in Comparative Example 3; Fig.31 This is the it curve of CoOx prepared in Comparative Example 3. DETAILED DESCRIPTION The present invention is further described below in conjunction with the accompanying drawings and embodiments. The following embodiments are explanations of the present invention and the present invention is not limited to the following embodiments: Materials and reagents: sodium tetrachloropalladate, anhydrous ruthenium chloride, cobalt chloride hexahydrate, oleylamine, ethanol, concentrated hydrochloric acid, toluene; Instruments and equipment: electronic balance, magnetic stirrer, separating funnel, stainless steel autoclave, desktop centrifuge, vacuum drying oven, muffle furnace, electrochemical workstation. Example 1 A method for preparing Pd-RuCoOx nanoparticles comprises the following steps: S1. Weigh 0.005M sodium tetrachloropalladate and dissolve it in 1mL concentrated hydrochloric acid. Dilute it to 50mL with deionized water, then add 0.005M anhydrous ruthenium chloride and 0.020M cobalt chloride hexahydrate to form a uniform solution A. S2. Prepare 50 mL of ethanol solution containing 8% oleylamine and mix it evenly with the solution obtained in step S1 to obtain solution B; S3. 50 mL of toluene was added to solution B and stirred thoroughly, then transferred to a separatory funnel and the toluene layer was taken; S4. The toluene layer solution obtained in step S3 was transferred to a corrosion-resistant liner and placed in a 100 mL stainless steel autoclave for a solvothermal reaction at a reaction temperature of 180° C. for a reaction time of 24 h to obtain a solid component; S5. Collect the solid components in step S4, clean them and place them in a vacuum drying oven at 60 ° C for 8h to obtain a powder material for standby use; S6. The powder material obtained in step S5 is placed in a muffle furnace and calcined at a temperature of 300° C., a calcination time of 2 h, and a heating rate of 2.5° C. / min to obtain Pd-RuCoOx-1 nanoparticles. Example 2 A method for preparing Pd-RuCoOx nanoparticles comprises the following steps: S1. Weigh 0.005M sodium tetrachloropalladate and dissolve it in 1mL concentrated hydrochloric acid. Dilute it to 50mL with deionized water, then add 0.005M anhydrous ruthenium chloride and 0.025M cobalt chloride hexahydrate to form a uniform solution A. S2. Prepare 50 mL of ethanol solution containing 8% oleylamine and mix it evenly with the solution obtained in step S1 to obtain solution B; S3. 50 mL of toluene was added to solution B and stirred thoroughly, then transferred to a separatory funnel and the toluene layer was taken; S4. The toluene layer solution obtained in step S3 was transferred to a corrosion-resistant liner and placed in a 100 mL stainless steel autoclave for a solvothermal reaction at a reaction temperature of 180° C. for a reaction time of 24 h to obtain a solid component; S5. Collect the solid components in step S4, clean them and place them in a vacuum drying oven at 60 ° C for 8h to obtain a powder material for standby use; S6. The powder material obtained in step S5 is placed in a muffle furnace and calcined at a temperature of 300° C., a calcination time of 2 h, and a heating rate of 2.5° C. / min to obtain Pd-RuCoOx-2 nanoparticles. Example 3 A method for preparing Pd-RuCoOx nanoparticles comprises the following steps: S1. Weigh 0.005M sodium tetrachloropalladate and dissolve it in 1mL concentrated hydrochloric acid. Dilute it to 50mL with deionized water, then add 0.005M anhydrous ruthenium chloride and 0.030M cobalt chloride hexahydrate to form a uniform solution A. S2. Prepare 50 mL of ethanol solution containing 8% oleylamine and mix it evenly with the solution obtained in step S1 to obtain solution B; S3. 50 mL of toluene was added to solution B and stirred thoroughly, then transferred to a separatory funnel and the toluene layer was taken; S4. The toluene layer solution obtained in step S3 was transferred to a corrosion-resistant liner and placed in a 100 mL stainless steel autoclave for a solvothermal reaction at a reaction temperature of 180° C. for a reaction time of 24 h to obtain a solid component; S5. Collect the solid components in step S4, clean them and place them in a vacuum drying oven at 60 ° C for 8h to obtain a powder material for standby use; S6. The powder material obtained in step S5 is placed in a muffle furnace and calcined at a temperature of 300° C., a calcination time of 2 h, and a heating rate of 2.5° C. / min to obtain Pd-RuCoOx-3 nanoparticles. Comparative Example 1 The difference between this comparative example and Example 3 is that anhydrous ruthenium chloride is not added, specifically as follows: A method for preparing Pd-CoOx nanoparticles comprises the following steps: S1. Weigh 0.005M sodium tetrachloropalladate and dissolve it in 1mL concentrated hydrochloric acid, dilute it to 50mL with deionized water, and then add 0.030M cobalt chloride hexahydrate to form a uniform solution A; S2. Prepare 50 mL of ethanol solution containing 8% oleylamine and mix it evenly with the solution obtained in step S1 to obtain solution B; S3. Measure 50 mL of toluene and add it to solution B and stir thoroughly, transfer it into a separatory funnel and take the toluene layer; S4. The toluene layer solution obtained in step S3 was transferred to a corrosion-resistant liner and placed in a 100 mL stainless steel autoclave for a solvothermal reaction at a reaction temperature of 180° C. for a reaction time of 24 h to obtain a solid component; S5. Collect the solid components in step S4, clean them and place them in a vacuum drying oven at 60 ° C for 8h to obtain a powder material for standby use; S6. The powder material obtained in step S5 is placed in a muffle furnace and calcined at a temperature of 300° C., a calcination time of 2 h, and a heating rate of 2.5° C. / min to obtain Pd-CoOx nanoparticles. Comparative Example 2 The difference between this comparative example and Example 3 is that sodium tetrachloropalladate is not added, specifically as follows: A method for preparing RuCoOx nanoparticles comprises the following steps: S1. Weigh 0.005 M anhydrous ruthenium chloride and 0.030 M cobalt chloride hexahydrate and dissolve them in 50 mL deionized water to form a uniform solution A; S2. Prepare 50 mL of ethanol solution containing 8% oleylamine and mix it evenly with the solution obtained in step S1 to obtain solution B; S3. Measure 50 mL of toluene and add it to solution B and stir thoroughly, transfer it into a separatory funnel and take the toluene layer; S4. The toluene layer solution obtained in step S3 was transferred to a corrosion-resistant liner and placed in a 100 mL stainless steel autoclave for a solvothermal reaction at a reaction temperature of 180° C. for a reaction time of 24 h to obtain a solid component; S5. Collect the solid components in step S4, clean them and place them in a vacuum drying oven at 60 ° C for 8h to obtain a powder material for standby use; S6. The powder material obtained in step S5 is placed in a muffle furnace and calcined at a temperature of 300° C., a calcination time of 2 h, and a heating rate of 2.5° C. / min to obtain RuCoOx nanoparticles. Comparative Example 3 The difference between this comparative example and Example 3 is that anhydrous ruthenium chloride and sodium tetrachloropalladate are not added, and the details are as follows: A method for preparing CoOx nanoparticles comprises the following steps: S1. Weigh 0.030 M cobalt chloride hexahydrate and dissolve it in 50 mL deionized water to form a uniform solution A; S2. The solution obtained in step S1 was mixed with 50 mL of an ethanol solution containing 8% oleylamine to obtain a solution B; S3. 50 mL of toluene was added to solution B and stirred thoroughly, then transferred to a separatory funnel and the toluene layer was taken; S4. The toluene layer solution obtained in step S3 was transferred to a corrosion-resistant liner and placed in a 100 mL stainless steel autoclave for a solvothermal reaction at a reaction temperature of 180° C. for a reaction time of 24 h to obtain a solid component; S5. Collect the solid components in step S4, clean them and place them in a vacuum drying oven at 60 ° C for 8h to obtain a powder material for standby use; S6. The powder material obtained in step S5 is placed in a muffle furnace and calcined at a temperature of 300° C., a calcination time of 2 h, and a heating rate of 2.5° C. / min to obtain CoOx nanoparticles. The Pd-RuCoOx nanoparticles prepared in Examples 1-3 of the present invention, the Pd-CoOx nanoparticles prepared in Comparative Example 1, the RuCoOx nanoparticles prepared in Comparative Example 2, and the CoOx nanoparticles prepared in Comparative Example 3 were used as working electrodes in the electrocatalytic oxygen evolution reaction. Specifically, a saturated calomel electrode and a platinum wire electrode were selected as a reference electrode and a counter electrode, respectively; 5 mg of Pd-RuCoOx-1 nanoparticle catalyst was weighed and dispersed into 1 mL of a mixed solution, wherein the solution included: 0.5 mL of water, 0.5 mL of ethanol, and 20 μL of naphthol solution. The above solution was ultrasonicated for 30 minutes to obtain a slurry, which was evenly coated on a 1 cm 2 The working electrode was obtained by drying on carbon paper. The electrolyte used in the electrocatalytic oxygen evolution test was 0.05 mol / L H2SO4 solution, and the scanning rate was 2 mV·s -1 . For Pd-RuCoOx-1 nanoparticles, Figure 2 The XRD diffraction pattern shows that Pd-RuCoOx-1 has a high degree of crystallinity and its main components are RuO2, Pd and Co3O4; Pd-RuCoOx-1 is assembled into spherical particles with uniform size and a diameter of no more than 500nm ( Figure 3 ); at 10mA / cm 2 The required voltage is 1.502V ( Figure 4 ); the Tafel slope is 87.49mV / dec( Figure 5 ); After 10 hours of reaction in acidic medium, the activity of Pd-RuCoOx-1 decreased by 12.7%, but it still maintained good activity ( Figure 6 ); It can be seen that the prepared Pd-RuCoOx-1 has the characteristics of uniform size and low oxygen evolution potential, and the synthesis method has good controllability, mild reaction conditions, and is relatively environmentally friendly. For Pd-RuCoOx-2 nanoparticles, Figure 7 The XRD diffraction pattern shows that Pd-RuCoOx-2 has a high degree of crystallinity and its main components are RuO2, Pd and Co3O4; Pd-RuCoOx-2 is assembled into spherical particles with uniform size and a diameter of no more than 500nm ( Figure 8 ); at 10mA / cm 2 The required voltage is 1.547V ( Fig. 9 ); the Tafel slope is 86.87mV / dec( Fig.10 ); After 10 hours of reaction in acidic medium, the activity of Pd-RuCoOx-2 decreased by 13.3%, but it still maintained good activity ( Fig.11 ); It can be seen that the prepared Pd-RuCoOx-2 has the characteristics of uniform size and low oxygen evolution potential, and the synthesis method has good controllability, mild reaction conditions, and is relatively environmentally friendly. For Pd-RuCoOx-3 nanoparticles, Fig.12 The XRD diffraction pattern shows that Pd-RuCoOx-3 has a high degree of crystallinity and its main components are RuO2, Pd and Co3O4; Pd-RuCoOx-3 is assembled into spherical particles with uniform size and a diameter of no more than 500nm ( Fig.13 ); at 10mA / cm 2 The required voltage is 1.559V ( Fig.14 ); the Tafel slope is 90.64mV / dec( Fig.15 ); After 10 hours of reaction in acidic medium, the activity of Pd-RuCoOx-3 decreased by 14.1%, but it still maintained good activity ( Fig.16 ); It can be seen that the prepared Pd-RuCoOx-3 has the characteristics of uniform size and low oxygen evolution potential, and the synthesis method has good controllability, mild reaction conditions, and is relatively environmentally friendly. For Pd-CoOx nanoparticles, Fig.17The XRD pattern shows that the main components of the material are Pd and Co3O4; Pd-CoOx has an irregular particle morphology, and the size of the nanoparticles is uneven, ranging from 100nm to 1μm ( Fig.18 ); at 10mA / cm 2 The required voltage is 1.652V ( Fig.19 ); the Tafel slope is 106.68mV / dec( Fig. 20 ); Fig.21 It can be seen from the it curve that the activity of Pd-CoOx has decayed by 46% after 5 hours of stability test in 0.05 mol / L H2SO4 solution. It can be concluded from this comparative example 1 that the Pd-CoOx material prepared without the precious metal Ru has large and uneven size, high oxygen evolution potential and poor stability. For RuCoOx nanoparticles, Fig. 22 The XRD pattern shows that the main components of the material are RuO2, Co3O4 and CoO; RuCoOx presents irregular nanoparticle morphology and is accompanied by agglomeration ( Fig.23 ); at 10mA / cm 2 The required voltage is 1.662V ( Fig.24 ); the Tafel slope is 113.7mV / dec( Fig.25 ); Fig.26 It can be seen from the it curve that the activity of RuCoOx has decayed by 75% after 5 hours of stability test in 0.05 mol / L H2SO4 solution. It can be concluded from this comparative example 2 that the RuCoOx material prepared without the precious metal Pd has large size and agglomeration, high oxygen evolution potential and poor stability. For CoOx nanoparticles, Fig. 27 The XRD pattern shows that the prepared materials are Co3O4 and CoO; CoOx has irregular particle morphology, and the average size does not exceed 500nm ( Fig.28 ); at 10mA / cm 2 The required voltage is 1.765V (such as Fig.29 ); Tafel slope is 99.72mV / dec( Fig.30 ); Fig.31 It can be seen from the it curve that the activity of CoOx has decayed by 36% after 5 hours of stability test in 0.05 mol / L H2SO4 solution. It can be concluded from this comparative example 3 that the CoOx material prepared without precious metals is large and uneven in size, has a high oxygen evolution potential, and has poor stability. The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the art can make many possible changes and modifications to the technical solution of the present invention by using the above disclosed methods and technical contents without departing from the spirit and technical solution of the present invention, or modify it into an equivalent embodiment of equivalent changes. Therefore, any simple modification, equivalent replacement, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of protection of the technical solution of the present invention.

Claims

1. A method for preparing Pd-RuCoOx nanoparticles, characterized in that: The following steps are involved: S1. Weigh sodium tetrachloropalladate and dissolve it in concentrated hydrochloric acid, dilute it with deionized water, and then add cobalt chloride and ruthenium chloride to form a uniform solution A; S2. Prepare an ethanol solution containing oleylamine and mix it evenly with the solution obtained in step S1 to obtain a solution B; S3. Add toluene to solution B, stir thoroughly, transfer to a separatory funnel and take the organic solvent layer; S4. The organic solvent layer obtained in step S3 is placed in an autoclave for a solvothermal reaction to obtain a solid component; S5. Collect the solid components in step S4, clean them, and dry them to obtain a powder material for later use; S6. The powder material obtained in step S5 is placed in a muffle furnace and calcined to obtain Pd-RuCoOx nanoparticles.

2. The method for preparing Pd-RuCoOx nanoparticles according to claim 1, characterized in that: In step S1, the molar ratio of sodium tetrachloropalladate to ruthenium chloride is 1:1-1:3, the feeding concentration of sodium tetrachloropalladate is 0.001-0.01M, the feeding concentration of ruthenium chloride is 0.001-0.03M; and the concentration of cobalt chloride is 0.01-0.05M.

3. The method for preparing Pd-RuCoOx nanoparticles according to claim 1, characterized in that: The content of oleylamine in the ethanol solution in step S2 is 5-20%; the ratio of the ethanol solution containing oleylamine to the solution A obtained in step S1 is 1:

1.

4. The method for preparing Pd-RuCoOx nanoparticles according to claim 1, characterized in that: The volume ratio of toluene to solution B in step S3 is 1:

1.

5. The method for preparing Pd-RuCoOx nanoparticles according to claim 1, characterized in that: The temperature of the solvent thermal reaction in step S4 is 180-220° C., and the reaction time is 24-30 hours.

6. The method for preparing Pd-RuCoOx nanoparticles according to claim 1, characterized in that: In step S5, the drying temperature is 60-80° C. and the drying time is 6-12 hours.

7. The method for preparing Pd-RuCoOx nanoparticles according to claim 1, characterized in that: In step S6, the calcination temperature is 300-500° C., the calcination time is 2-4 hours, and the heating rate is 2-5° C. / min.

8. The Pd-RuCoOx nanoparticles prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The diameter of the Pd-RuCoOx nanoparticles is ≤500nm.

9. Use of the Pd-RuCoOx nanoparticles according to claim 8 in oxygen evolution reaction in an acidic environment.